Ricoeur’s Hermeneutic Study on Anti-Corruption Campaign Posters in Mengwitani Village - Halim, Bobby; Arimbawa, I Made Gede; Kurniawan, Herdy; Hakim, Muhammad Rivan (Gorga : Jurnal Seni Rupa, 2025)
The history of Mengwitani Village provides a context for understanding corruption in Bali. Despite progress, corruption persists due to power struggles, lack of transparency, and low accountability. The case of the former Village Head who was caught in a Village Fund corruption scandal illustrates how violations can occur even at the local government level, undermining public trust. Corruption, rooted in historical vulnerabilities, has become a means to maintain power and wealth at the expense of the community. In response, the Mengwitani Village Head created Anti-Corruption posters that were published on the village's official website. The purpose of hermeneutical research on the anti-corruption campaign posters in Mengwitani Village is to interpret the meaning contained in the posters, reveal the anti-corruption messages they want to convey, and understand how anti-corruption values are communicated visually to the people of Mengwitani Village. Analyzing this campaign using Paul Ricoeur's hermeneutic approach provides a comprehensive perspective. The method used is a qualitative descriptive research method. Examining the visual structure reveals symbolic elements, such as the depiction of evil figures, which are used to emphasize violations of law and ethics. The hermeneutic approach helps reveal the deeper message of the posters: changing public perception to prevent corruption. The main targets are the community and the State Civil Apparatus (ASN), whose responses shape the effectiveness of the campaign. Understanding the industrial context highlights the advertisement as a complex cultural artifact with significant social and political implications. Ricoeur's analysis not only deciphers the poster's message but also explores its broader meaning in the socio-political landscape of Mengwitani Village.